Determinants of Reproductive Tract Infection among married women in rural and peri-urban areas of Aligarh: A cross sectional Study - Sharma, Shivangi; Mehnaz , Saira; Ansari, Mohammad Athar; Abedi, Ali Jafar (Indian Journal of Community Health, 2022)
Background: Reproductive Tract Infections (RTI) have a direct impact on reproductive and child health through infertility, cancers, and pregnancy complications, and they have an indirect impact through their role in facilitating the sexual transmission of the human immunodeficiency virus. Objectives: To find the prevalence and determinants of RTI/STI among married women of reproductive age group in rural and peri-urban areas of Aligarh. Methods: The data were collected by using a pretested, semi-structured with both open and closed-ended questionnaire from 500 married women of reproductive age group. The collected data were analyzed using IBM SPSS 20.0 Proportion, frequencies, ?2, and logistic regression were used to interpret the data. Results: Prevalence of RTI/STI symptoms was found to (42.8%) in rural areas and 37.6 % in peri-urban areas. Strong association was found in study subjects having lower educational status, who were not using any contraceptive method, not following good menstrual hygiene, early marriage age had husband history of RTI/STI, had a history of abortion, had a history of violence, and increased parity. Conclusions: Prevalence of symptoms found to be associated with these females having low educational status, early age of marriage, high parity, partner history of reproductive Tract Infections, history of violence etc. So, there should be more focus on improvement in these factors to reduce the prevalence.